(untitled) (Educational Dimension, 2023)
The purpose of the study is to determine the features of online lectures, essential characteristics and possibilities of implementing strategies for their implementation in the training of future primary school teachers. The research was conducted with students of the first (bachelor’s) and second (master’s) levels of higher education in the speciality 013 Primary education of one of the state universities of Ukraine. For its implementation, the analysis of literature was carried out in the direction of scientific research, which made it possible to determine the conceptual apparatus and theoretical basis of this study. Based on this, strategies for quality training of future primary school teachers were determined. What found practical implementation in the construction of the structure of the online lecture, which will contribute to its effective conduct. Based on the generalization of practical experience for each of the structural parts of the online lecture, means, tools and techniques that promote active interaction, student involvement and reflection have been selected and organized. We see prospects for further research on this topic: in the development and improvement of existing strategies and structures of online lectures for effective training of future primary school teachers; in the study of the impact of online lectures on academic achievement and motivation of students; in the development and implementation of new technologies and tools to improve the quality of online lectures. The results of the study can be used by scientists, teachers of higher education institutions, academic leaders and managers to ensure high-quality and effective training of future primary school teachers in the online environment.